The Provenance of Regolith at the Chang'e‐5 Candidate Landing Region. Issue 5 (15th May 2020) - Xie, Minggang; Xiao, Zhiyong; Zhang, Xunyu; Xu, Aoao
Abstract: The upcoming lunar Chang'e‐5 mission is scheduled to land near Mons Rümker, in northern Oceanus Procellarum, and return samples with masses up to 2 kg from depths up to 2 m. A clear understanding of the regolith components in the candidate landing region is crucial to both the selection of sampling sites and the interpretation of the geological affinities for the returned samples. We quantitatively estimate the abundance of distantly sourced particles (DSPs) in the regolith at the landing region using an updated ballistic sedimentation model. Our results suggest that older units have a higher abundance of DSPs. In the targeted landing area, the total abundance of DSPs on the surface of the regolith varies from approximately 12% to 20%, and most of the DSPs on the surface are ejecta from the Pythagoras ( 5%) and/or Aristarchus ( 7%) craters. The youngest geological unit, which is located in the easternmost sector of the landing region, possesses the least DSPs in the regolith. Therefore, sampling the eastern unit has a higher potential of revealing both the petrological characteristics and age of the youngest mare basalt, which are fundamentally important to improve both the lunar crater chronology and the understanding of late‐stage evolution of the Moon. Our results also indicate that the anorthositic material within the shallow regolith is most likely ejected from the Pythagoras and Aristarchus craters, which could further improve the understanding of lunar geology and chronology. Plain Language Summary: Chang'e‐5 will be the first lunar sample return mission since the 1976 Luna 24 mission. It will return surface and core samples with masses up to 2 kg from depths up to 2 m from northern Oceanus Procellarum. Most of the returned samples are expected to be lunar regolith. A better understanding of the regolith components in the candidate landing region is therefore helpful to both select sampling sites and interpret the samples that will be returned in the future. Here, we estimate the abundance of distantly sourced particles (DSPs) in the regolith within the proposed landing region. We find that older units are more enriched in DSPs, and the total surface abundance of DSPs varies from approximately 12% to 20%. Most DSPs on the surface are ejecta from the Pythagoras ( 5%) and/or Aristarchus ( 7%) craters. Our results support that the youngest mare unit is most suitable for sample return because of the low abundance of DSPs. Furthermore, core samples from this unit contain not only local basaltic materials and the several major sources of distant ejecta in the regolith but also both pristine highland anorthosites and pyroclastic deposits. Key Points: We estimate the abundance of distantly sourced particles in the regolith in the Chang'e‐5 candidate landing region The most abundant distantly sourced particles are ejecta from the craters Pythagoras and/or Aristarchus It is recommended to return samples from the youngest mare surface as there is a low abundance of distantly sourced particles